New Deletion at Promoter of HBG1 Gene in Sickle Cell Disease Patients With High HbF Level. Issue 1 (January 2020) - Chaouch, Leila; Sellami, Houssem; Kalai, Miniar; Darragi, Imen; Boudrigua, Imen; Chaouachi, Dorra; Abbes, Salem; Mnif, Samia
Abstract : Objectives: The 5′ upstream region of the HBG1 gene plays a very important role in the expression of fetal hemoglobin (HbF). In contrast, increased HbF levels can inhibit the deoxygenation-induced polymerization of sickle hemoglobin (α2βS2), which leads to moderation at the clinical level among sickle cell disease (SCD) patients. Thus, we focused on this article on the study of the 5′ upstream region of HBG1 among SCD pediatric patients with high levels of HbF. Materials and Methods: Fifteen SCD pediatric patients were chosen during the first time of diagnosis, and the HbF values were determined before hydoxyurea treatment. The ages at entry ranged from 1 to 8 years. The mutational screening of the 5′ upstream region of the HBG1, which extends to −587 bp, was performed by polymerase chain reaction/sequencing. Results: HbF values range from 6.9% to 26%. Sequencing results showed the presence of 6 known polymorphisms, which are as follows: RS35993903, RS34844625, RS3020750, RS2860456, RS2860470, and RS12290216. Interestingly, we also found a new deletion of GCAG in the HBG1 promoter at position -273. Conclusions: We described a new mutation, which is a deletion of GCAG in the HBG1 promoter at position -273. This deletion could affect a binding site of a transcription factor unknown so far and thus modulate the expression of the HBG1 gene.